2019
DOI: 10.1155/2019/8082195
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Solubility of Curcumin Metal Complexes and Investigating Some of Their Biological Activities

Abstract: This article describes the synthesis of curcumin complexes with metal ions. Properties of these complexes such as spectra IR and UV-Vis and solubility were investigated. The optimum parameters of ultrasound to enhance the solubility was figured out as follows: the capacity of ultrasound: 750 W/g; the time of ultrasound: 7 min; the concentration of the surfactant Tween 80 : 2%. The maximum solubility (mg/ml) of complexes was as follows: Cur-Fe(III): 0.162 ± 0.01; Cur-Zn(II): 0.267 ± 0.02; and Cur-Ca(II): 0.417 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…These results suggest that physical mixtures between CR and CA do not improve or enhance the pharmacological effects of curcumin compared to the complexes that it can form with heavy metals, including copper. These complexes that are chemically synthesized have been shown to have a better effect than curcumin itself and even decrease the toxicity of metals [16,51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that physical mixtures between CR and CA do not improve or enhance the pharmacological effects of curcumin compared to the complexes that it can form with heavy metals, including copper. These complexes that are chemically synthesized have been shown to have a better effect than curcumin itself and even decrease the toxicity of metals [16,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, due to regulations on the use of antibiotics in poultry production derived from the problems of bacterial resistance, and considering that S. Typhimurium is a bacterium capable of developing antimicrobial resistance more quickly than other Salmonella species [12,13], several strategies have been proposed to treat and control Salmonella infections [14]. Despite the large number of alternatives that have been tried, it has been reported that the combination of polyphenolic compounds with metal ions, such as copper, can enhance their antioxidant, anti-in ammatory, and antimicrobial effects, with the additional advantage that the toxicity of metal ions is reduced by the formation of complexes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The obtaining of metal complexes of curcumin with Zn 2+ and Cu 2+ was reported in different research studies [ 78 , 79 ]. Previous studies have shown that the wavelength at which the absorption had a maximum value for the curcumin/metal ions complexes was different from that of FC [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the metal, it is possible to have the chelation reaction in solvents that do not cause the problems for environmental issues that can occur with organic solvents. For example, Hieu et al [14] synthesized metal-curcumin complexes by mechanical mixing of metal chloride salts and curcumin (metal ion:curcumin 1:1 mol with Zn 2+ ; 1:3 with Fe 3+ ) in a mortar until homogenous powder mixtures were obtained. A propylene glycol:water (1:1 v/v) solution was added to the mixtures followed by mechanical shaking and drying at 60 • C to obtain powdered complexes of curcumin metal ion.…”
Section: Synthesis Of the Curcumin-metal Complexesmentioning
confidence: 99%